An Analysis of Sense Relations in Alice in Wonderland 2: Through the Looking Glass Movie - Metha Wulandari; Sastika Seli; Yulfi Yulfi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
The problems of the research were â€what are the kinds, dominant use, and meaning of sense relations used in Alice in Wonderland 2: through the Looking Glass Movie?â€. The objectives of the research were to explain the kinds, dominant use, and meaning of sense relations used in Alice in Wonderland 2: through the Looking Glass Movie. The researcher used a qualitative descriptive method to clasify and analyze the data. The data were analyzed through some steps including identification, classification, reduction, description, and conclusion. After the data were analyzed, the reseacher found the kinds, the dominant use, and the meaning of sense relations used in Alice in Wonderland 2: through the Looking Glass Movie. Sense relations in Alice in Wonderland 2: through the Looking Glass Movie were analyzed in term synonymy, polysemy, homonymy, hyponymy, and antonymy. The reseacher found synonymy 160 words (52%) as the dominant use, the second dominant use is hyponymy 70 words (23%), the third dominant use is antonymy 68 words (22%), the fourth dominant use is homonymy 6 words (2%), the fewest kind is polysemy 2 words (1%). The meaning which has found was analyzed based on speaker sense and linguistic sense. The researcher found 5 words as speaker sense and almost all of the meaning of sense relations has linguistic sense because the meaning of word is lexical meaning based on the dictionary. Key word: Sense Relations, Movie